PENGGUNAAN METODE DISKUSI PADA MATA PELAJARAN IPS UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD NEGERI 018 PULAU KIJANG KECAMATAN RETEH - Syafridas Syafridas (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is based on the learning result of Social Scienc Students of Grade V SD Negeri 018 Pulau KijangKecamatan Reteh which is still very low. This study aims to improve the learning outcomes of Social Sciences.From the data analysis of teacher activity at meeting 1 cycle I get the value of 65% (good) and at the secondmeeting increased to 75% (good). In the second cycle of the third meeting the value of teacher activity increasedagain to 85% (very good) and at the fourth meeting increased to 90% (very good). Judging from the activities ofstudents also experienced an increase from 70% (good) to 80% (very good). In the second cycle of the thirdmeeting to 85% (very good) and at the fourth meeting increased to 90% (very good). Judging from the results ofthe students also experienced preningkat, from the average score of students on the basic score of 61.35. afterthe first cycle the average student score increased to 73.90 with an increase of 12.55 points from the baselinescore. In the second cycle, student learning outcomes also experienced an increase of 13.85 points from cycle Iwith an average of 87.75 students. It can be concluded that the advancement of the discussion model, canimprove the learning outcomes of Social Sciences of students of class V SD Negeri 018 Pulau Kijang KecamatanReteh.